Knowledge on prevention of complications related to immobility among caregivers of orthopedic patients at selected hospitals of Chitwan district - Poudyal, S; Neupane, M; Lopchan, M (Journal of Chitwan Medical College, 2015)
Immobility is a condition in which a person is unable to move freely or is restricted for therapeutic reasons. Immobility affects all systems of the body leading to complications. The objective of the study is to find out the knowledge on prevention of complications related to immobility among caregivers of orthopedic patients admitted on orthopedic ward of Chitwan Medical College Teaching Hospital (CMCTH), College of Medical Sciences Teaching Hospital (CMSTH) and Bharatpur Hospital, Chitwan. The study design was descriptive, cross sectional and 133 caregivers were interviewed by using semistructured interview schedule. Data was analyzed by using SPSS and various tests such as frequency distribution, chisquare and odds ratio. The study findings revealed that 45.9% of respondents were from adjacent districts of Chitwan, 45.9% were between age group 16-30 years, 56.4% were female, 84.2% were married and 70.7% were literate. The highest mean knowledge score of caregivers was in the area of joint contracture (44.4%) followed by bedsore (39.3%), hypostatic pneumonia (37.6%), urinary tract infection (32.1%) and least mean knowledge score was in the area of deep vein thrombosis(25.2%) and constipation (25.1%) respectively. The level of knowledge is statistically significant with area of residence (p=0.038), marital status (p=0.020) and educational status (p=0.001) of respondents. The study concluded that caregivers had poor knowledge regarding preventive measures. Awareness programme need to be planned and implemented. DOI: http://dx.doi.org/10.3126/jcmc.v4i3.11932 Journal of Chitwan Medical College 2014; 4(3): 9-12